On the Carbenic Nature of Nitrile Ylides: Experimental and Computational Characterization of Hydroxy and Amino Nitrile Ylides - Nunes, Claudio M.; Jesus, A. J. Lopes; Rosado, Mario T. S.; FAUSTO, RUI (Wiley-VCH Verlag, 2024)
Nitrile ylides are 1,3-dipolar species with structures that are commonly described by propargylic and/or allenic resonance forms. Nevertheless, certain nitrile ylides exhibit a tendency to form dimers, suggesting the existence of structures characterized by an important carbenic contribution. To address the nitrile ylide carbenic nature, here we investigate two derivatives with OH and NH2 electron-donating substituents. These nitrile ylides were generated in cryogenic matrices by UV-irradiation of 3-hydroxy- and 3-amino-isoxazole precursors and were found to photoisomerize to the corresponding oxazoles. The IR spectral characterization of the photogenerated nitrile ylides reveals the absence of the characteristic strong nu as(CNC) absorption, which is associated with allenic and propargylic type structures. Computed geometries for the two experimentally investigated nitrile ylides and for analogues with different substituents at C3 and C1, together with NBO and NRT electronic structure analyses, performed at the CCSD(T) level of theory, reveal substantial carbenic character exclusively for nitrile ylides bearing OH and NH2 substituents at C3. As a whole, the results shed light on the factors determining the structural features of nitrile ylides, which play a major role in defining the reactivity of these important elusive compounds.
Keywords: Carbenes; Computational Chemistry; Geometric and Electronic Structure; Matrix-isolation Ir Spectroscopy; Nitrile Ylides